Walter Benjamin and Günther Anders on Kafka and the Role of Literature - Seri, Bat Chen (Labyrinth, 2025)
What is the political significance of literature? How, if at all, can fictional narratives interact with issues of social and legal justice? This paper addresses these questions and proposes four models of literature's intervention in political reality based on Walter Benjamin’s and Günther Anders’ readings of Kafka. According to Benjamin’s 1930s Kafka essays, fictional narratives have the power to unsettle hitherto established legal decisions and thus partake in the exercise of justice. Anders, in his 1951 book Kafka: Pro und Contra, criticises Kafka for authoring narratives that—complacent with existing power—lend themselves to being used to morally absolve acts of oppression. Taken together, the four models—two of which are based on Benjamin's Kafka reading and two on Anders'—offer a complex view of the role of literature as a political actor, recognising its positive value while warning against its potential abuse.